Pillars Of Community : Four Rules of Pre-Benedictine Monastic Life - Kardong, Terrence (Book collections on Project MUSE., 2010)
"Anyone who has explored a great Romanesque church has been impressed, even awed, by the mighty stone foundations supporting the great central tower. As four pillars give a firm base to these soaring structures, so four ancient Rules stand beneath the foundations of Western monasticism, giving a structure on which later spiritual architects, Benedict among them, would build. In this book Terrence Kardong explores the lives and Rules of four of the earliest monastic writers - Basil, Pachomlus, Augustine, and the anonymous author of the rules of Lerins. In engaging fashion he shows how the lives and social milieux of these earliest founders shaped their monasticism." "Yet as varied as these Rules are, they are based on the same fundamental understanding of what a Christian monk and a Christian community should be; thus they furnish a solid foundation for the great edifice still to come."--Jacket.